Construction of Legal Justice, Certainty, and Benefits in the Supreme Court Decision Number 46P/HUM/2018 - Jahar, Asep Saepudin; Hazmi, Raju Moh; Adhha, Nurul (Jurnal Cita Hukum, 2021)
The philosophical discourse on legal justice, certainty, and benefits paradigm in the reality of Indonesian law reflect a strong indication of legal positivism in the Supreme Court decision. It causes a loss in the sense of justice and the hope for the community to meet legislative candidates with a clean track record and full of integrity. This study is normative-philosophical legal research applying the theory of justice developed by John Stuart Mill and John Rawls in highlighting the concept of legal justice, certainty, and benefits. The construction of justice in this decision applies the concept of justice as fairness as seen in the court consideration focusing on individual freedom (political rights to vote and to be elected). This is taken to protect the natural rights which are irreplaceable by any other rights. Meanwhile, the use of legal benefits and certainty is to reinforce the legal positivism paradigm. As the result, the study shows the three legal values (justice, certainty, and benefits) share equal positions in the country’s legal framework.Keywords: Legal Justice; Legal Certainty; Legal Benefits; Law; Supreme Court Decision Konstruksi Keadilan, Kepastian, dan Kemanfaatan Hukum dalam Putusan Mahkamah Agung Nomor 46P/HUM/2018 Abstrak Wacana filosofis paradigma keadilan, kepastian, dan kemanfaatan hukum dalam realitas hukum Indonesia mencerminkan indikasi kuat positivisme hukum dalam putusan Mahkamah Agung. Hal tersebut menyebabkan hilangnya rasa keadilan dan harapan masyarakat untuk bertemu calon legislatif dengan rekam jejak yang bersih dan penuh integritas. Penelitian ini merupakan penelitian hukum normative-filosofis yang menerapkan teori keadilan yang dikembangkan oleh John Stuart Mill dan John Rawls dalam menyoroti konsep keadilan, kepastian, dan kemanfaatan hukum. Konstruksi keadilan dalam putusan ini menggunakan konsep keadilan sebagai fairness yang terlihat dalam pertimbangan pengadilan yang menitikberatkan pada kebebasan individu (hak politik untuk memilih dan dipilih). Hal ini dijadikan pertimbangan untuk melindungi hak alami yang tidak dapat digantikan oleh hak lainnya. Sedangkan kemanfaatan dan kepastian hukum dijadikan pertimbangan untuk memperkuat paradigma positivisme hukum. Hasilnya, studi ini menunjukkan bahwa ketiga nilai hukum (keadilan, kepastian, dan manfaat) memiliki kedudukan yang sama dalam kerangka hukum negara. Kata Kunci: Keadilan hukum, kepastian hukum, kemanfaatan hukum, hukum, putusan Mahkamah Agung. Конструирование справедливости, определенности и преимущества закона в Постановлении № 46P/HUM/2018 Верховного суда АннотацияПостановление Верховного суда № 46P/HUM/2018 вызвало раскол в правовой парадигме в Индонезии. Философский дискурс между справедливостью, определенностью и преимуществами закона в реальности индонезийского законодательства отражает сильные симптомы правового позитивизма в постановлении Верховного суда. Это приводит к потере чувства справедливости и надежды сообщества на получение репутации чистых и порядочных кандидатов. Данное исследование является нормативно-философским правовым исследованием. Подход, основанный на теории справедливости Джона Стюарта Милля и Джона Ролза, был использован для понимания концепции справедливости, преимущества и правовой определенности в постановлении. Конструирование справедливости в постановлении использует концепцию справедливости как равенства (справедливость как честность), что можно увидеть из соображений судей, подчеркивающих индивидуальную свободу (политические права, право быть избранным и голосовать) как форму попытки отстоять либертарианские права или естественные права, которые не могут быть отменены свободой других людей. Между тем аспекты преимущества и определенности подчеркивают позитивную парадигму закона. В этом исследовании сделан вывод о том, что три юридические значимости (определенность, преимущество и справедливость) занимают не менее важное место в рамках правовой системы страны.Ключевые Слова: Справедливость; определенность; преимущество закона; закон; постановление Верховного суда.